Immigration et cheminements scolaires aux études supérieures au Canada : qui y va et quand ? Une analyse longitudinale à partir du modèle de Cox - Kamanzi, Pierre Canisius; Bastien, Nicolas; Doray, Pierre; Magnan, Marie-odile (Canadian Journal of Higher Education, 2016)
This article aims to compare the educational pathways of young Canadian immigrants to those of their counterparts from non-immigrant families. To this end, we apply the Cox’s proportional hazard risk model. The results obtained from the longitudinal data from the Youth in Transition Survey (YIT) show that, in general, the risk of access to higher education is higher for students with an immigrant background than for their native peers. The variance ranges from 3 to 35 percentage points in first-generation immigrants and from 4 to 12 percentage points in second-generation immigrants. In addition, significant differences within youth with immigrant background were found with regard to the age of higher education entry, their persistence and the type of degree obtained by the age of 24. These differences are relatively reduced when one controls for the parents’ resources, as well as the student’s secondary school experience but remained statistically significant.